Comparative Evaluation of Magnesium and Dexmedetomidine as Adjuvants to Ropivacaine in Caudal Block in Children - A Randomized Control Trial - Megha Gandotra; Smriti Gulati; Naine Bhadrala; Rajesh Mahajan; Shruti Gupta; Shipra Gupta (Dr. Annil Mahajan, 2023)
Background: Children often receive inadequate analgesia because of the fear of adverse effects of analgesic drugs and also because of difficulty in assessment of pain in children. Caudal block is one of the safe armamentaria used for perioperative anaesthesia and analgesia in children. Aims and Objectives: Our aim is to compare duration of post operative analgesia and sedation score between dexmedetomidine and magnesium when used as adjuvants to ropivacaine in caudal block in pediatric age groups in lower abdominal surgeries. Materials & Methods: This randomized clinical study included 90 patients of ASA group I or II in the age group of 2-10 years undergoing lower abdominal surgeries under general anesthesia with caudal block supplementation. They were divided in three groups as Group C received 1 ml of normal saline Group M received magnesium Sulphate (50?mg) in 1 ml normal saline and Group D received dexmedetomidine 1μg/kg in 1?ml normal saline in addition to 0.2% ropivacaine in a dose of 1ml/kg to all participants. Results: There was no significant difference demographic and surgical characters among the three groups (p>0.05). However, there was a decrease in mean heart rate of 10-15 % in Group D as compared to the other two groups. The duration of post operative analgesia was significantly prolonged in Groups M and D, with an increase in sedation seen in Group D as compared to other groups. Conclusion: Dexmedetomidine and magnesium significantly increased the duration of post-operative analgesia when given as adjuvants to ropivacaine in caudal block in children undergoing lower abdominal surgeries.